Performance characterization of a heat pipe-enhanced heat pump for corn drying in the Philippines - Macaranas, Raymund Joseph P. (2008)
The energy performance of a closed-loop heat pipe-enhanced heat pump dryer was evaluated for its application in corn drying at Philippine climatic conditions. Twelve (12) drying operation trials were conducted during the harvest season in Malaybalay, Bukidnon (Southern Philippines) in September 2006 where ambient temperature ranged from 20-30ºC. Temperature of the heated air ranged from 37 to 41ºC with an airflow rate of about 1,764.4 cubic feet per minute. To dry 1,700-1,800 kilogram of corn in about 17 hours, the dryer required 5 kilowatts of electric energy input. It pumped 11.5 kilowatts of heat (or 41, 239 kJ/hr) to dry a batch of corn with an initial moisture content of 32% to 14% final moisture content at base grain depth of 7.2 feet. The heat-pipe enhanced heat pump was found to have a drying efficiency of 92% and a Coefficient of Performance of 2.3. Compared to the conventional kerosene-fired mechanical dryers, the heat utilization of the heat pipe-enhanced heat pump was lower by 58%. The energy cost, was lower by 67% than the 6-ton capacity flat bed dryer and 51% lower that the a conventional re-circulating batch type dryer.